INVESTIGATING THE RESPONSE MECHANISMS OF JAPONICA RICE (ð˜–ð˜³ð˜ºð˜»ð˜¢ ð˜´ð˜¢ð˜µð˜ªð˜·ð˜¢ L.) UNDER DIFFERENT MID-HIGH-LATITUDES OF NORTHEAST CHINA FOR BETTER FUTURE ADAPTATION - Shahbaz Farooq, Muhammad; Maqbool, Zubaira; Fatima, Hira (REVISTA DE AGRICULTURA, 2022)
This study showed the response characteristics of rice under different climatic conditions which has an important practical and theoretical significance. The objectives of this study were to establish reasonable production measures and theoretical foundation for adjusting the Japanese rice system through investigation of response mechanisms at mid-high latitudes. Replacing time with space, 4 cultivars (late maturing; Longdao-18, Longdao-21, early maturing; Longjing-21, Suijing-18) were selected, the experiment was conducted at Heilongjiang province during 2017 and 2018. The time difference for superior and inferior grains reaching the peak point of the grain-filling curve showed obvious difference, indicating the difference of climatic conditions had different degrees of influence on each cultivar. A great influence on the dry weights of the grain-filling of the Suijing-18 and Longjing-21 was noticed, whereas the dry weights and grain-filling rates were found less affected for Longdao-21 and Longdao-18. Most of the grain filling was seen during the middle period at Harbin as the filling period was divided into three phases ie, early, middle and late, which observed almost 60% of the whole grain filling process. Furthermore, non-adaptability of cultivars to a specific environment or combination of prevailing conditions could cause yield variation. Values for yield components were high at Qiqihar; therefore, there was more potential to get higher yield. The protein and amylose contents, and fine rice rate were higher at Harbin whereas brown rice and chalkiness percentages were higher at Qiqihar.min and earlier transplantation will produce taller plants. It has been indicated that higher temperature on earlier anthesis at the start of the day thereby increased the probability of escape from higher temperatures stresses later during the day. Earlier anthesis under humid conditions will provide potential escape from rising ambient temperatures during the day.